A REVIEW: ADVANCE IN FROZEN DOUGH IMPROVER TECHNOLOGY OF BREAD - Bahlina Mohd Nur; Cut Nilda (LPPM UNIVERSITAS KAHURIPAN KEDIRI, 2019)
Bread is food that has a short shelf life and some chemical and physical changes during the storage. One effort that can be improved these deficiencies is by making frozen dough. This article aims to gain information related to processing of frozen dough, the factors that affect its damage and the latest technology in the process of frozen dough. Frozen dough is bread dough stored in freezing after the moulding stage. This method can extend bread shelf life by preventing contamination of microorganisms. Innovation in frozen dough technology aims to reduce physical and chemical changes such as freezing technology assisted by ultrasound, pre-treatment of frozen dough, addition of special ingredients, and frozen storage conditions. Key words : bread, frozen dough, storage